Numerical Investigation on Characteristics of Fluid Flow Over Cavity in a Parallel Channel at Low Reynolds Numbers - Nguyen Hung Khanh; Lanh Le Thanh; Thoi Le Nam (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The database management output system is interesting and available in the numerical analysis of fluid flow, especially for a fluid flowing past a cavity inside a channel. The aim of the current study is to investigate numerical simulations characteristic of fluid flowing over a cavity in a parallel channel at low Reynolds numbers and to predict reduced energy. Computer Fluid Dynamic (CFD) is utilized to solve two-dimensional low Reynolds Navier-Stoke equations with support from Gambit software, which incorporates a simulation modelling suite in the meshing model. The numerical simulations were carried out by fluid such as water for the Reynolds numbers of 50 and 1000 and for cavity aspect ratio, W/H, of 1/3, 1/2, 1, 2, and 3. The normal mean velocity input is unity. This investigation indicated that changing cavities aspect ratio influences vortex flow significantly. Besides, the study found that the aspect ratio of cavities and Reynolds numbers influence total pressure and temperature output significantly and are important for most fluid dynamic problems. Finally, the optimal reduced pressure in a channel and optimal design cavities geometries yield better results.